Patterns of Care for Stage II-III Rectosigmoid Cancers in the United States, 2004-2015. (May 2020) - Sanford, Nina N.; Aguilera, Todd A.; Beg, Muhammad S.; Sanjeevaiah, Aravind; Hong, Theodore S.; Wo, Jennifer Y.; Folkert, Michael R.
Abstract : Objectives: Although current guidelines continue to recommend trimodality therapy for stage II to III rectal cancers, a lower incidence of local recurrence has been observed in patients with upper rectal tumors, including those in the rectosigmoid. In practice, patients with upper rectal tumors may not be receiving all 3 modalities of therapy. Patterns of care for patients with rectosigmoid cancers have not previously been described. Methods: The National Cancer Database (NCDB) was used to identify patients diagnosed with stage II to III rectosigmoid cancer who underwent definitive surgery between 2004 and 2015. Multivariable logistic regression defined adjusted odds ratio and associated 95% confidence intervals of receipt of any pelvic radiotherapy and preoperative and postoperative pelvic radiotherapy. Multivariable logistic regression also assessed odds of treatment with any chemotherapy and multiagent chemotherapy. Results: Among 8410 patients, 3566 (42.4%) received any pelvic radiotherapy, of which 2516 (70.6%) were treated with preoperative radiotherapy. Factors associated with receipt of radiotherapy included male sex, white race, younger age, positive clinical nodes and positive margins ( P <0.001). Among patients with clinically positive nodes, 1980 (48.6%) received any radiotherapy and among those with pathologically positive nodes, 1532 (37.9%) received radiotherapy. A total of 5708 patients (67.9%) received any chemotherapy including 3020 (52.9%) with multiagent chemotherapy. A total of 2579 (30.7%) of the cohort was treated with surgery alone and among patients who were T3N0, this proportion rose to 42.5%. Conclusions: Less than half of patients with stage II to III rectosigmoid cancers are treated with radiation therapy and approximately one third do not receive chemotherapy. Ongoing and future studies may help to better tailor treatment for rectosigmoid tumors to optimize the therapeutic ratio. Our work may serve as a benchmark on which to compare future practice patterns. Abstract : Supplemental Digital Content is available in the text.